The Bush leadership, the power of ideas, and the war on terror - MacDonald, David Bruce; Nabers, Dirk 1968-; Patman, Robert G (Routledge, 2012)
This volume explores the relationship between President George W. Bush's leadership, the administration's stated belief in the power of ideas (and the ideas of power) and its approach to the war on terror. Drawing on the international expertise of ten American foreign policy and security specialists, this incisive and timely book combines theoretical perspectives on political leadership with rigorous empirical analysis of selected aspects of the Bush administration's post 9/11 foreign policy